Preparatioon and characterisation of cellulose-based hydrogel derived from sugarcane bagasse - Kanchana, Karunakaran (Universiti Malaysia Sarawak (UNIMAS), 2016)
Hydrogels were produced by di solving regenerated cellulose in NaOH/urea solution by using citric acid (CA) as a cross-linker, by two methods, which were heating and freezing. The surface morphology and properties of hydrogel was characterised using SEM and water absorption testing. After HN03, NaOH and H~2 pre-treatment, treated sugarcane bagasse (SCB) was dissolved in NaOHffhiourealUrea solution and generated using ethanol. Hydrogels produced by heating method had better swelling ratio and reswelling kinetic than that of hydrogel formed by freezing method. With the increase in cellulose concentration and CA cross-linker, the swelling ratio of the hydrogels reduced, while the reswelling kinetics increased. Most of the hydrogels showed rnacroporous structure in SEM images. Heating hydrogels were more transparent compared to freezing hydrogel . Hence, structure and properties of hydrogels could be changed by varying the cellulose concentrations and CA concentrations.